PENGARUH TERAPI ZIKIR TERHADAP PENURUNAN KECEMASAN PASIEN PRA OPERASI DI RSUD DR. ACHMAD MOCHTAR BUKITTINGGI - Renidayati Reni (Jurnal Keperawatan Sehat Mandiri, 2026)
Surgery is an invasive medical procedure that often causes anxiety in preoperative patients. Unresolved anxiety can impact the patient's physiological and psychological conditions, such as increased blood pressure, sleep disturbances, and slowed recovery. One non-pharmacological intervention that can be used to reduce anxiety is dhikr therapy. Dhikr therapy provides a relaxing and calming effect through a spiritual approach, thus helping patients better prepare for surgery. This study used a quasi-experimental design with a one-group pretest-posttest approach. The study was conducted from August 11, 2025, to May 29, 2026. The study sample consisted of 30 respondents selected using a purposive sampling technique. Data collection was carried out using the Hamilton Rating Scale for Anxiety (HARS) questionnaire to assess the level of preoperative anxiety in patients. Data analysis was performed using the Shapiro-Wilk test and continued with the Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed a decrease in the average level of anxiety in patients before and after receiving dhikr therapy. The results of statistical tests showed a significant effect of dhikr therapy on reducing preoperative anxiety in patients with a p-value of 0.000 (p < 0.05). The conclusion of this study is that dhikr therapy can be used as an effective, safe, easy-to-do, and minimally side-effect complementary intervention to reduce anxiety in preoperative patients. Hospital nurses are expected to provide dhikr therapy intervention services to patients experiencing preoperative anxiety.